Plasma xanthine oxidoreductase activity in Japanese patients with type 2 diabetes across hospitalized treatment. Issue 8 (18th December 2020) - Kawachi, Yusuke; Fujishima, Yuya; Nishizawa, Hitoshi; Nagao, Hirofumi; Nakamura, Takashi; Akari, Seigo; Murase, Takayo; Taya, Naohiro; Omori, Kazuo; Miyake, Akimitsu; Fukuda, Shiro; Takahara, Mitsuyoshi; et al.
Abstract: Aims/Introduction: Xanthine oxidoreductase (XOR) is an enzyme that catalyzes hypoxanthine and xanthine to xanthine and uric acid, respectively. Plasma XOR activity has recently been measured in humans. However, limited information is known about plasma XOR activity in patients with type 2 diabetes mellitus, and its changes after short‐term glycemic control treatment. Materials and Methods: We enrolled 28 Japanese patients (10 men/18 women) with type 2 diabetes mellitus who were hospitalized to undergo medical treatment for diabetes. Plasma XOR activity, quantified using triple quadrupole mass spectrometry and liquid chromatography, and other clinical parameters were examined at admission and 2 weeks after treatment during hospitalization. Changes in plasma XOR activity after treatment during hospitalization and associated clinical parameters were assessed. Results: At the time of admission, the median plasma XOR activity was 83.1 pmol/h/mL, with a wide range of 14.4–1150 pmol/h/mL. Multiple regression analysis identified serum aspartate transaminase and alanine transaminase levels as significant and independent factors correlating with the baseline plasma XOR. Two weeks of treatment during hospitalization was associated with a significant decrease in plasma XOR activity. Changes in serum aspartate transaminase were also the only significant and independent factor correlating with changes in plasma XOR activity. Conclusions: A close relationship was observed between plasma XOR activity and liver transaminases in patients with type 2 diabetes mellitus, cross‐sectionally, and also across treatment during hospitalization. Abstract : In diabetes patients, baseline plasma xanthine oxidoreductase activity was associated with aspartate transaminase and alanine transaminase. After treatment during hospitalization, plasma xanthine oxidoreductase activity was significantly decreased. By the treatment, Δ aspartate transaminase was the only independent factor for Δ plasma xanthine oxidoreductase activity.